(untitled) (Bangladesh Journal of Pharmacology, 2011)
The present study shows the phytochemical analysis and antibacterial activity of leaf and callus of Centella asiatica. Leaf explants of C. asiatica were cultured on MS medium supplemented with different concentration of plant growth regulators for callus initiation. The maximum percentage of callusing was achieved in medium supplemented with 6-benzylaminopurine 4.0 mg/Land 2,4-dichlorophenoxyacetic acid 2.0 mg/L. In the preliminary phytochemical screening, alkaloids, glycosides, terpenoids, steroids, flavonoids, tannins, saponins and reducing sugars were present in most of the tested extracts of leaf and in vitro grown callus of C. asiatica. Methanol, acetone, chloroform and water extracts of leaf and callus were evaluated for in vitro antibacterial activity against Bacillus cereus, Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa by agar plate well diffusion method. All the extracts from leaf and callus of C. asiatica showed significant antibacterial activity against the tested organisms. However, methanol extracts of leaf and callus showed maximum inhibitory effect.